PROFESIONALISME GURUiDALAMiMENINGKATKANiMUTU PENDIDIKANiPADA MASAiPANDEMIiCOVID-19 - Anita Komalasari; Yessi Fitriani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2021)
Abstrak“Profesionalisme” dan “guru”memiliki suatu makna bahwa profesionalisme guru merupakan kemampuan yang dimiliki oleh guru sebagai tenaga kependidikkan yang memiliki suatu peranan penting untuk melakukanitugas pokoknyaisebagai tenagaipendidik danipengajar yang menjalankan pekerjaannya dengan penuh tanggungjawab diantaranya meliputi; kemampuan dalamimerencanakan, melakukan, idan melaksanakanievaluasiipembelajaran. Metodeipenelitian yangidigunakan adalah kajian pustakaidan wawancaraikepada salahisatu guruiatau tenaga pendidik di sebuah sekolah melalui via media sosial pada kegiatan prosesibelajar mengajariselama masaipandemiicovid-19 ini, ada hambatan dan sebagainya yang dihadapi oleh guru atau tenaga pendidik untuk menjadi pendidik yang profesional. Pada masa wabah pandemiicovid-19 iniidapat  melumpuhkan duniaipendidikan dalam proses kegiatanibelajarimengajar (KBM). Meskipun demikian proses kegiatan belajar mengajar (KBM) berjalan walaupun tidak seindah tatap muka, belajar dilakukan dengan menggunakan dalam jaringan (daring) yang menuntut guru sebagai tenaga pendidik untuk dapat menguasai bidang ilmu pengetahuan teknologi (IT) agar keprofesioanalisme berjalan dan bertanggungjawab yakni dengan menggunakan berbagai aplikasi media sosial melalui gawai whaatshaff, telegram, E-Learning, qualitiva, classrooom, ruang guru, mesengger,zoom,google meet,fb, dan sebagainya. Hal ini menuntut guru atau tenaga pendidik dapat profesional juga dalamimenggunakan mediaisosial. Pembelajaranipada masaipandemiicovid-19 ini sejak lebih kurang 2 tahun terakhir ini baik dari tingkatan PAUD,TK, SD, SMA/MA/SMK, maupun Perguruan Tinggi (PT) dituntut mampu mengikuti perkembangan zaman pembelajaran Daring Online atau PembelajaraniJarakiJauh (PJJ). kata kunci: Profesionalisme,guru, mutu, pandemi,covid-19 Abstract The ”profesionalisme” and “teacher” have a meaning that teacher professionalism is an ability possessed by teachers as educators who have an important role to carry out their main duties as educators and teachers who carry out their work with full responsibility including the ability to plan, carry out, and implement learning evaluation. Theiresearch methodiused is a literature review andiinterviews withioneiof theiteachers or educators in a school via social media. And initeaching andilearning activitiesiduringithe covid-19ipandemicivirus, there areiobstacles and so on that are faced by the teacher or educators to become professional educators. During in theicovid-19 pandemic, it paralyzed theiworld ofieducationiin theiprocess ofiteaching andilearningiactivities. However, theiprocess of teaching andilearning activities about walking, although don,t as beautiful as face to face, the learning a carried out using a network that requires teachers as educators to beiable masterithe field ofiscience anditechnology (IT) so professionalism can run and be responsible, namely by using various social media applications through devices. whaatshaff, telegram, elearning, qualitiva, classrooom, teacher room, messenger, zoom, google meet, fb, and so on. This requires teachers or educators to be professional also in using social media. iLearning duringitheicovid-19 pandemic since the last 2 years, both from PAUD, TK, SD, SMA/MA/SMK, and Higher Education (PT) levels areirequired toibe ableito follow theidevelopments ofithe era of Online Online learning or Distance Learning (PJJ).Keywords : ”profesionalism” and “teacher” quantity,pandemic,covid- Abstract The ”profesionalisme” and “teacher” have a meaning that teacher professionalism is an ability possessed by teachers as educators who have an important role to carry out their main duties as educators and teachers who carry out their work with full responsibility including the ability to plan, carry out, and implement learning evaluation. Theiresearch methodiused is a literature review andiinterviews withioneiof theiteachers or educators in a school via social media. And initeaching andilearning activitiesiduringithe covid-19ipandemicivirus, there areiobstacles and so on that are faced by the teacher or educators to become professional educators. During in theicovid-19 pandemic, it paralyzed theiworld ofieducationiin theiprocess ofiteaching andilearningiactivities. However, theiprocess of teaching andilearning activities about walking, although don,t as beautiful as face toface, the learning a carried out using a network that requires teachers as educators to beiable masterithe field ofiscience anditechnology (IT) so professionalism can run and be responsible, namely by using various social media applications through devices. whaatshaff, telegram, elearning, qualitiva, classrooom, teacher room, messenger, zoom, google meet, fb, and so on. This requires teachers or educators to be professional also in using social media. iLearning duringitheicovid-19 pandemic since the last 2 years, both from PAUD, TK, SD, SMA/MA/SMK, and Higher Education (PT) levels areirequired toibe ableito follow theidevelopments ofithe era of Online Online learning or Distance Learning (PJJ).